Concordance of cancer drug therapy information derived from routinely collected hospital admissions data and the Systemic Anti-Cancer Therapy (SACT) dataset, for older women diagnosed with early invasive breast cancer in England. (April 2023) - Gannon, Melissa Ruth; Park, Min Hae; Miller, Katie; Dodwell, David; Horgan, Kieran; Clements, Karen; Medina, Jibby; Cromwell, David Alan
Abstract: Background: Evaluating uptake of oncological treatments, and subsequent outcomes, depends on data sources containing accurate and complete information about cancer drug therapy (CDT). This study aimed to evaluate the consistency of CDT information in the Hospital Episode Statistics Admitted Patient Care (HES-APC) and Systemic Anti-Cancer Therapy (SACT) datasets for early invasive breast cancer (EIBC). Methods: The study included women (50 + years) diagnosed with EIBC in England from 2014 to 2019 who had surgery within six months of diagnosis. Concordance of CDT recorded in HES-APC (identified using OPCS codes) and SACT was evaluated at both patient-level and cycle-level. Factors associated with CDT use captured only in HES-APC were assessed using statistical models. Results: The cohort contained 129, 326 women with EIBC. Overall concordance between SACT and HES-APC on CDT use was 94 %. Concordance increased over the study period (91–96 %), and there was wide variation across NHS trusts (lowest decile of trusts had concordance≤77 %; highest decile≥99 %). Among women receiving CDT, 9 % (n = 2781/31693) of use was not captured in SACT; incompleteness was worst (18 %=47/259) among women aged 80 + and those diagnosed in 2014 (21%=1121/5401). OPCS codes in HES-APC were good at identifying patient-level and cycle-level use of trastuzumab or FEC chemotherapy (fluorouracil, epirubicin, cyclophosphamide), with 89 % and 93 % concordance with SACT respectively (patient-level agreement). Among cycles of solely oral CDT recorded in SACT, only 24 % were captured in HES-APC, compared to 71 % for intravenous/subcutaneous CDT. Conclusions: Combining information in HES-APC and SACT provides a more complete picture of CDT treatment in women aged 50 + receiving surgery for EIBC than using either data source alone. HES-APC may have particular value in identifying CDT use among older women, those diagnosed less recently, and in NHS trusts with low SACT data returns. Highlights: Evaluating uptake of cancer drug therapy (CDT), and subsequent outcomes, requires complete information in data sources. Patient-level data on aspects of breast cancer care, including CDT activity, are routinely collected in hospitals. We combined information on CDT use recorded in hospital admissions data and routinely-collected treatment data. This provided a more complete picture of CDT treatment use among women receiving surgery for early invasive breast cancer.